Propriedades vibracionais, ópticas, eletroquímicas e térmicas de três derivados do ácido de Meldrum e vibracionais e estruturais de uma base de Schiff complexada com Zn - Silva, João Antunes da (2021)
In this work, the vibrational properties of a Schiff base complexed with Zinc and the vibrational, optical, electrochemical and thermal properties of three 5- aminomethylene Meldrum acid derivatives were studied. For the bis(4E)-4-(2- hidroxybenzylideneamino) -1,2-dihydro -2,3-dimetyl -1- phenylpyrazol-5-one (GM1Zn) metal complex, Raman spectroscopy measurements were performed at room temperature in the spectral region between 50 to 3500 cm-1 and infrared in the region of 400 to 3500 cm-1, DFT calculations were performed, being possible the assignment of vibrational modes through analysis based on the potential energy distribution (PED). A comparison of theoretical and experimental spectra allowed us to interpret the results where the metal ion coordinated with two imine nitrogens and two pyrazolone oxygens. The vibrational, optical, electrochemical and thermal properties of Meldrum acid derivatives 5- aminomethylene MPYM, HYM and CNYM were investigated combining Infrared and Raman spectroscopy at room temperature assisted by DFT calculations, UV–vis spectroscopy assisted by TD-DFT calculations, cyclic voltammetry and thermal analysis. The B3LYP / 6− 311++G (d, p) calculations led to the identification of the minimums on the potential energy surfaces of the molecule, from these calculations the most stable conformer in relation to the dihedral angle C8-N1-C7-C4 was predicted. Comparison between experimental and theoretical vibrational spectra provides an accurate understanding of the fundamental vibrational modes and leads to a better interpretation of experimental Raman and infrared spectra. The vibrational mode assignment given in terms of potential energy distribution analysis (PED) leads us to a broader interpretation of the vibrational spectra of the investigated material. The UV–vis spectrum of the compound was recorded in the region between 200 and 450 nm and the HOMO and LUMO electronic properties were calculated by TDDFT. The thermal stability of the compounds was obtained based on data from the TG-DTA analysis.